PENGABDIAN MASYARAKAT BERBASIS TEKNOLOGI: “INSTALASI VSAT DAN TRANSFER PENGETAHUAN SISTEM KOMUNIKASI SATELIT DI PPICURUG” - fatonah, Feti; Wildan, Muh.; Sulistyo, Didik; Anggraini, Dian; Eriyandi, Eriyandi; Toni, Toni; Sulaiman, M.Arif; Wahyudi, Johan; Roza, Febrian; G, Gilang Erlangga; F, Annisa Brianna; A, Febrian Latief (MAJU : Indonesian Journal of Community Empowerment, 2025)
This community service activity aims to enhance satellite communication technology learning facilities at the Indonesian Civil Aviation Polytechnic Curug (PPIC) through the installation of a VSAT (Very Small Aperture Terminal) system in the Communication, Navigation, and Surveillance (CNS) Laboratory. VSAT was selected due to its ability to provide connectivity independently of conventional cable infrastructure, making it highly relevant for the practical needs of students and cadets in the field of communication technology. The activities included an explanation of ground-based satellite systems, installation of satellite modems, network system configuration, and training on basic usage and maintenance for lecturers, lab technicians, and students of the communication engineering program. The results showed that with the satellite connectivity now available in the PPIC laboratory, practical training in communication particularly for students in the Air Navigation Engineering Study Program, is now supported, and participants demonstrated an increased understanding of VSAT-based satellite communication systems